A licence to drive? Neurological illness, loss and disruption. Issue 7 (22nd May 2018) - Stepney, Melissa; Kirkpatrick, Susan; Locock, Louise; Prinjha, Suman; Ryan, Sara
Abstract: The sense of freedom and independence that being able to drive generates may be taken for granted by many until it is threatened by illness. Drawing on the 'mobility turn' in social sciences that emphasises the social and emotional significance of the car (Sheller and Urry2000, 2006 ), this article presents secondary analysis of narratives of driving and its significance across four neurological conditions (epilepsy, Parkinson's disease, transient ischaemic attack and motor neurone disease). Taking an interactionist approach we explore how the withdrawal of a driving licence can represent not just a practical and emotional loss of independence, but also loss of enjoyment; of a sense and feeling of 'normal' adulthood and social participation; and of an identity (in some cases gendered) of strength and power. Conversely the ability to keep driving can maintain an unbroken thread of narrative, for example enabling people with speech difficulties to feel and look normal behind the wheel. Moments of pleasure and normality illuminate the importance of examining the micro‐strands of disruption illness can cause.